Implementasi Forward Chaining dan Metode Simpleks untuk Menentukan Ransum Unggas yang Ekonomis - Wildan Mahmud (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Poultry need food to maintain their lives and to produce. To meet the needs of these nutritional elements, poultry eat from various types of food. Because there is no single food ingredient that contains a complete nutritional element, so we need a variety of appropriate and balanced food ingredients to meet nutritional needs. This can be done by choosing cheap food ingredients without ignoring the quality of the nutritional content that is adjusted to the type and age of poultry. To solve the above problems, an expert system with a forward chaining method can be used to determine the nutritional needs and nutritional content of food ingredients, while linear programming with the simplex method is used to determine the combination of poultry feed-forming ingredients that meet economical poultry nutritional needs. The combination of the forward chaining method and the simplex method can accelerate the preparation of combinations of food ingredients, so that the resulting application can provide a solution in making decisions for the selection of food ingredients forming ration effectively